Unraveling the impact of cultural distance on IT outsourcing success – insights from three major sourcing reconfigurations. Issue 3 (24th June 2020) - Könning, Michael; Strahringer, Susanne; Westner, Markus
Abstract : Purpose: IT outsourcing (ITO) has developed into an established practice for organizations but the interorganizational and oftentimes international collaboration it involves comes at a price: Reports from academia and practice suggest that more than 25% of all ITO projects fail, many because of cultural differences between client and provider organizations. Against this background, this paper analyzes the complex nature of cultural distance and its multi-faceted effect on ITO success. Design/methodology/approach: This paper builds upon extant literature on culture on the national, organizational and team level, conceptualizes its effect on relationship quality and ITO success, and hypothesizes a model on potential moderators and management techniques to offset culture-induced challenges. It then evaluates and refines the model by means of an interpretive qualitative research design for an in-depth single-case study of ProSiebenSat.1 Media SE (P7S1), a leading European media company that reconfigured its IT sourcing model three times in 10 years. Findings: The results from interviews with top managers from client and provider organizations represent one of the first integrated views on the critical importance of cultural compatibility on multiple levels, provide manifold examples for its complex effect on ITO success, as well as moderators and potential management techniques to promote ITO success. Research limitations/implications: This paper contributes relevant empirical insights to the growing body of literature on culture and its underestimated role in ITO success. It builds on tentative theory that is confirmed and refined. Practical implications: The paper helps in substantiating the complex and intangible nature of culture and demonstrates means for its effective management. Originality/value: The results from interviews with top managers from client and provider organizations represent one of the first integrated views on the critical importance of cultural compatibility on multiple levels, provide manifold examples for its complex effect on ITO success, as well as moderators and potential management techniques to promote ITO success.